Public Health and Labor Policy - Charlotte Justine Diokno Sicat; Valerie Gilbert Ulep; Robert Hector G. Palomar; Ricxie B. Maddawin; Mark Gerald C. Ruiz (Philippine Institute for Development Studies (PIDS), 2023)
The COVID-19 pandemic, and lockdown measures taken to control its spread, brought economies to a halt, turning the public health crisis into an economic one. Though government responses, such as labor and social welfare protection programs, were similar for recent economic crises like the Global and Asian Financial Crises, the origin of the current crisis being public health rather than financial markets, put the spotlight on the health sector and the need for its strengthening both to manage COVID-19 and ensure sustainable economic recovery. This study examines the relationship between health spending and labor productivity. Will the COVID-19 pandemic crisis trigger more meaningful public investments in health? How can we build back better health policy for labor productivity? Answering these questions requires establishing that health policy and indicators are associated with measures of labor productivity. If there is such evidence, there is a need to examine prepandemic public health expenditures and policies and compare these to health policies of comparable countries with better health outcomes. This would provide policy makers guidance in improving health sector outcomes and overall productivity. This sought evidence of the association of health policy and indicators with labor productivity on two levels, across: (1) comparable ASEAN countries and (2) Philippine regions. The results showed that public health expenditures were robust and significant for GDP per capita (across ASEAN countries) and regional GDP per worker (RGDP, Philippine regional estimations). This suggests that increased public health spending is associated with increased labor productivity. For the cross-country results, life expectancy and gross capital investments were also found to be positively significant, indicating increased productivity with a longer life (i.e., a healthier population), and with physical capital/tools and infrastructure (consistent with neoclassical growth theory or NGT). For Philippine regional regressions, only the proportion of the working age population was found to be significant but negative, possibly suggesting that a bigger work force is associated with lower productivity (ceteris paribus, this is consistent with NGT and the law of diminishing marginal product).
Keywords: 330; labor demand; labor supply; neoclassical growth theory